The role of N(6)-methyladenosine (m6a) modification in cancer - Xiaozhou Xie; Zhen Fang; Haoyu Zhang; Zheng Wang; Jie Li; Yuchen Jia; Liang Shang; Feng Cao; Fei Li (EXCLI Journal : Experimental and Clinical Sciences)
N(6)-methyladenosine (m6A) modification is the most abundant and prevalent internal modification in eukaryotic mRNAs. The role of m6A modification in cancer has become a hot research topic in recent years and has been widely explored. m6A modifications have been shown to regulate cancer occurrence and progression by modulating different target molecules. This paper reviews the recent research progress of m6A modifications in cancer and provides an outlook on future research directions, especially the development of molecularly targeted drugs.